Healthcare providers' level of involvement in provision of smoking cessation interventions in public health facilities in Kenya - Judy W. Gichuki; Rose Opiyo; Possy Mugyenyi; Kellen Namusisi (AOSIS, 2015)
Healthcare providers can play a major role in tobacco control by providing smoking cessation interventions to smoking patients. The objective of this study was to establish healthcare providers' practices regarding smoking cessation interventions in selected health facilities in Kiambu County, Kenya. This was a descriptive cross-sectional study carried out among healthcare providers working in public health facilities in Kiambu County, Kenya. Self-administered questionnaires were distributed to 400 healthcare providers selected using a two-stage stratified sampling technique. Only 35% of the healthcare providers surveyed reported that they always asked patients about their smoking status. Less than half (44%) reported that they always advised smoking patients to quit. Respondents who had received training on smoking cessation interventions were 3.7 times more likely to have higher practice scores than those without training (OR=3.66; 95%CI: 1.63-8.26; P=0.003). Majority of the healthcare providers do not routinely provide smoking cessation interventions to their patients. Measures are needed to increase health worker's involvement in provision of smoking cessation care in Kenya.